Simulation of capacitive pressure sensor based on microelectromechanical systems technology. (May 2018) - Baghelani, Masoud; Hosseini-Sianaki, Ahmad; Behzadi, Zeinab; Mirabdolah Lavasani, Arash
This paper proposes a very high sensitivity pressure sensor with a novel technique for temperature compensation. The proposed technique employs a geometrical method for self-compensation of Young's modulus reduction due to temperature increase, where a stronger spring with much larger length and width is anchored. According to the connection of the suspension spring to the larger spring, in higher temperatures, the large spring experiences more length increase, which in turn increases the stiffness of the suspension spring and, consequently, could compensates the Young's modulus reduction. Simulation results verify that the temperature variation related error in the compensated sensor is less than 0.66% of full-scale under 260 ℃ of temperature range, which shows considerable improvement in comparison with literature. The total consumed area is about 0.033 mm 2 with the sensitivity of 290 × 10 −6 K −1 .